Історико-правова характеристика статусу суддів та судового розсуду в країнах Західної Європи в період Середньовіччя - Кравчук, М.; Kravchuk, M. (Східноєвропейський національний університет імені Лесі Українки, 2019)
У статті проведено аналіз статусу суддів та судового розсуду у таких країнах, як Німеччина,Франція, Англія. На період Середньовіччя припадає формування та становлення судової системи більшості країн Західної Європи. На судовий розсуд впливали ряд чинників об’єктивного та суб’єктивного характеру. До таких чинників варто віднести соціально-економічне становище в державі, суспільний та економічний устрій, зокрема, соціальне становище, яке займали і вершителі правосуддя, і учасники процесу. Суттєвий вплив на дискрецію судді в період Середньовіччя мав ідеологічний (релігійний) чинник. The article represents the analysis of the status of judges and judicial discretion in such countries as Germany, France and England in the Middle Ages. The Middle Ages epoch witnessed first formation and establishment of the judicial system in most Western European countries. This process was greatly influenced by national traditions and social processes that occurred in each of the states. There were spiritual and secular courts, whose powers were almost identical. Consciousness and discretion of judges were formed under the influence of Christianity and the transformation of the approach to natural law; in the Renaissance period, they acquired a humanistic character. A number of factors influenced the process of administering justice and the status and discretion of the judge when making a decision (even if the judge was the head of the state). These factors include the socio-economic situation in the state, the social and economic system and in particular, the social status of both the judiciary and the participants in the process. The ideological (religious) factor had a significant effect on the discretion of a judge during the Middle Ages, since the dominant religion was of great significance for the content of the law, on the basis of which justice was carried out.
Historical and Legal Description of the Status of Judges and Judicial Discretion in the Countries of Western Europe during the Middle Ages
Keywords: статус суддів; судовий розсуд; Західна Європа; Середньовіччя; the status of judges; judicial discretion; Western Europe; the Middle Ages